Access to primary health care for asylum seekers and refugees: a qualitative study of service user experiences in the UK - Kang, Cara; Tomkow, Louise; Farrington, Rebecca (British journal of general practice, 2019)
Asylum seekers and refugees (ASR) face difficulty accessing health care in host countries. In 2017, NHS charges for overseas visitors were extended to include some community care for refused asylum seekers. There is growing concern that this will increase access difficulties, but no recent research has documented the lived experiences of ASR accessing UK primary health care. To examine ASR experiences accessing primary health care in the UK in 2018. This was a qualitative community-based study. ASR were recruited by criterion-based sampling through voluntary community organisations. A total of 18 ASR completed face-to-face semi-structured recorded interviews discussing primary care access. Transcripts underwent thematic analysis by three researchers using Penchansky and Thomas's modified theory of access. The qualitative data show that participants found primary care services difficult to navigate and negotiate. Dominant themes included language barriers and inadequate interpretation services; lack of awareness of the structure and function of the NHS; difficulty meeting the costs of dental care, prescription fees, and transport to appointments; and the perception of discrimination relating to race, religion, and immigration status. By centralising the voices of ASR and illustrating the negative consequences of poor healthcare access, this article urges consideration of how access to primary care in the UK can be enhanced for often marginalised individuals with complex needs.